The Two Wrong Reasoning and the Covid Pandemic - Groarke , Leo; Tindale, Christopher (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2023)
The crisis brought on by the COVID-19 pandemic led to a number of imposed measures that in other circumstances would be judged wrong or unreasonable. What allegedly warranted them was the urgency of the risks posed by COVID-19 and the belief that there were no alternative measures available. In this paper, we examine this kind of reasoning at different stages of the pandemic. We do so by developing a specific version of the argumentation scheme ‘Two Wrongs Reasoning’ which we apply to COVID-19 arguments. We conclude that the situations that were addressed were not as straightforward as many authorities and critics suggested – and that their reasoning about them often failed to recognize the complexity of two wrongs arguing; the nuanced balancing of wrongs that it requires; and the requirement that one seriously consider possible alternatives to any exceptional measures an argument proposes.